Metabolic syndrome and skin: Interactions and implications - Sujata Mehta Ambalal (Wolters Kluwer Medknow Publications, 2022)
The metabolic syndrome (MetS) has become a global crisis and is believed to affect almost one-quarter of the world's population. Its prevalence has been rising, especially in the younger age group. The interactions of the skin and MetS are myriad. Physiological functions of the skin may confer a protective role, whereas cutaneous diseases may play the role of MetS initiator or amplifier. Cutaneous signs may be some of the earliest manifestations of insulin resistance, the basic pathophysiology behind MetS. Skin changes are also prominent in type 2 diabetes mellitus, the consequence of MetS. Drugs used in dermatological disorders can lead to metabolic dysfunction. Awareness about the risk factors and early lifestyle interventions can help delay or even prevent the life-threatening complications of this syndrome. Dermatologists are in a unique position to predict and prevent MetS or its complications, a long time before the patient visits a physician for systemic problems. To write this review, an internet search was made focusing on articles on skin problems associated with MetS and its components, its risk factors, pathogenesis, and ways to prevent it. Information relevant to dermatological practice was compiled.